Post-reconstruction dermatitis of the breast. Issue 10 (October 2017) - Rosen, A.C.; Goh, C.; Lacouture, M.E.; Mehrara, B.J.; Cordeiro, P.G.; Myskowski, P.L.
Summary: Background: Approximately one-third of women diagnosed with breast cancer undergo mastectomy with subsequent implant-based or autogenous tissue-based reconstruction. Potential complications include infection, capsular contracture, and leak or rupture of implants with necessity for explantation. Skin rashes are infrequently described complications of patients who undergo mastectomy with or without reconstruction. Methods: A retrospective analysis of breast cancer patients referred to the Dermatology Service for diagnosis and management of a rash post-mastectomy and expander or implant placement or transverse rectus abdominis myocutaneous (TRAM) flap reconstruction was performed. Parameters studied included reconstruction types, time to onset, clinical presentation, associated symptoms, results of microbiologic studies, management, and outcome. Results: We describe 21 patients who developed a rash on the skin overlying a breast reconstruction. Average time to onset was 25.7 months after expander placement or TRAM flap reconstruction. Clinical presentations included macules and papules or scaly, erythematous patches and plaques. Five patients had cultures of the rash, which were all negative. Skin biopsy was relatively contraindicated in areas of skin tension, and was reserved for non-responding eruptions. Treatments included topical corticosteroids and topical antibiotics, which resulted in complete or partial responses in all patients with documented follow-ups. Conclusion: Our findings suggest that tension and post-surgical factors play a causal role in this hitherto undescribed entity: "post-reconstruction dermatitis of the breast." This is a manageable condition that develops weeks to years following breast reconstruction. Topical corticosteroids and antibiotics result in restoration of skin barrier integrity and decreased secondary infection.